2004
DOI: 10.1029/2003ja010064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoionization on propagation and branching of positive and negative streamers in sprites

Abstract: [1] Modeling studies indicate that double-headed streamers originating from single electron avalanches in lightning-driven quasi-static electric fields at mesospheric altitudes accelerate and expand, reaching transverse scales from tens to a few hundreds of meters and propagation speeds up to one tenth of the speed of light, in good agreement with recent telescopic, high-speed video and multichannel photometric observations of sprites. The preionization of the medium ahead of a streamer by the ionizing UV phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
551
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 299 publications
(625 citation statements)
references
References 79 publications
(198 reference statements)
70
551
3
1
Order By: Relevance
“…After the first claim [13] that a streamer filament within this deterministic continuum model in a sufficiently high field can evolve into an unstable state where it branches spontaneously, streamer branching was observed in more simulations [14,15,16]. While the physical nature of the Laplacian instability was elaborated in simplified analytical models [13,17,18,19,20], other authors challenged the accuracy of the numerical results [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first claim [13] that a streamer filament within this deterministic continuum model in a sufficiently high field can evolve into an unstable state where it branches spontaneously, streamer branching was observed in more simulations [14,15,16]. While the physical nature of the Laplacian instability was elaborated in simplified analytical models [13,17,18,19,20], other authors challenged the accuracy of the numerical results [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in many natural discharges and, in particular, for sprites above thunderclouds [15], it is appropriate to assume that the electric field is homogeneous. Of course, dust particles or other nucleation centers can play an additional role in discharge generation, but in this paper we will focus on the effect of a homogeneous field on a homogeneous gas.…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%
“…Another important assumption of the kinetic model is related to the exclusion of photochemistry processes occurring in sprites. Some photochemical mechanisms, like photoionization, might impact the propagation and branching of sprite streamers [Liu and Pasko, 2004;Bourdon et al, 2007] but with an indirect or minor influence on the non-equilibrium chemistry of the streamer plasma.…”
Section: Model Assumptions Parameters and Initial Conditionsmentioning
confidence: 99%
“…Sprites are thought to be produced by the QE field above the thunderstorm due to the fast removal of charges by CG flashes and their possible following continuous current (Pasko et al 1997;Liu and Pasko 2004;Liu et al 2015a). By carefully comparing the sprite occurrence time and the lightning location network data and ELF magnetic field recorded at Syowa station, it was found that the sprites occurring at 00:27 and 01:21, respectively, were produced by positive CGs with a single return stroke and the following continuous current.…”
Section: Thunderstorm Structure and Parent Flashesmentioning
confidence: 99%